Kecepatan penyusutan kuning telur dan panjang mutlak larva ikan nilem (Osteochilus hasselti) dengan aplikasi perbedaan dosis perendaman hormon tiroksin - Taufik Budhi Pramono; Najmiyatul Fajriyah; Sri Marnani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: One of Thyroid hormones that plays an important role in regulating fish physiology is thyroxine The aim of this research was to measure the yolk absorption and growth response of Nilem fish larvae with different doses of thyroxine hormone. Methods: We tested 4 doses and 3 replicates with immersion method. The data obtained was analyzed statistically, followed by the Tukey test assisted by SPSS 16.0 software. Supporting parameter data, temperature and air quality were analyzed descriptively using Microsoft Excel. Results The yolk sac absorption reached 99.99%, the survival 73% and absolute growth until 1.77 mm. Conclusion Before yolk sac ran out, the development of the Nilem larvae organ was fully completed. The optimal dose immersion of thyroxine hormone was 0.225 mg/L.